Koguduse kasvu missioloogilised mudelid - Lilleorg, Ago (Usuteaduslik Ajakiri, 2022)
The article presents the overview of church growth models as different church practices and approaches how church growth is understood and sought. These practices have emerged in a specific cultural and social environment, so their diversity is inevitable. These models are formulated by modeling the various practices which seek the growth of the church. The models of Church Growth discussed in this article are: Church Renewal and Revival; Home Church and Small Group; Church Growth; Church Health; Missional Church and Church Planting.